2010
DOI: 10.1016/j.ddmec.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of phospholipase A2-derived mediators in obesity

Abstract: Obesity has become an epidemic and its prevalence is increasing exponentially. A great deal of focus has been given to understanding the molecular processes that regulate obesity. The characterization of phospholipase A2s, especially adipose-specific PLA2, have lead to a proposed role of their downstream products in the progression of obesity and obesity related disorders. This review summarizes recent developments in the role of PLA2 and their downstream effects in the development of metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…In the HFD group, the levels of lysoPC 14:0, 18:0, and 20:3, and lysoPC-P 18:0 were increased, while the lysoPC 16:1, 18:2, and 20:5, and PC 34:2 and 34:0 levels were decreased compared to the ND group. LysoPC is converted from PC by phospholipase A2, which is activated under inflammatory conditions such as with a HFD [ 41 , 42 ]. Many studies showed lysoPCs as significant biomarkers of mice fed a HFD [ 8 ], overweight/obesity humans [ 23 ], and obesity-resistant BALB/c mice [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the HFD group, the levels of lysoPC 14:0, 18:0, and 20:3, and lysoPC-P 18:0 were increased, while the lysoPC 16:1, 18:2, and 20:5, and PC 34:2 and 34:0 levels were decreased compared to the ND group. LysoPC is converted from PC by phospholipase A2, which is activated under inflammatory conditions such as with a HFD [ 41 , 42 ]. Many studies showed lysoPCs as significant biomarkers of mice fed a HFD [ 8 ], overweight/obesity humans [ 23 ], and obesity-resistant BALB/c mice [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, adipose-specific PLA2 have received attention for potential anti-obesity and anti-diabetic roles. Both genetic and pharmacological inhibition of particular PLA2s has resulted in obesity-resistant mouse models, suggesting a potential to develop new drugs [39]. In addition, COX-2 has long been believed to play a role in the inflammatory process as a result of obesity with an HF diet [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…In the body, PLA2 hydrolyzes fatty acids (FA) from the sn-2 position of phospholipids to generate FA and lysophospholipids [26]. These products are tightly linked to obesity.…”
Section: Introductionmentioning
confidence: 99%